Lipid stores reveal the state of the coral-algae symbiosis at the single-cell level - Daniel Aagren Nielsen; Katherina Petrou (ISME Communications, 2023)
Abstract Coral reefs worldwide are threatened by environmental stress. The observable decline in coral cover, is principally due to the intensifying breakdown of the coral symbiosis, a process known as ‘bleaching’. Overproduction of reactive oxygen species (ROS) is considered a key driver of coral bleaching, where environmental stress leads to increased ROS expression. To explore the link between ROS damage and symbiont status, we measured lipid peroxidation (LPO), a ubiquitous form of ROS damage, in the lipid stores of individual endo- and ex-symbiotic algal cells of three coral species, using confocal microscopy and a lipid hydroperoxide sensitive fluorescent dye. We found LPO was higher in endosymbionts, while lipid volume was greater in ex-symbiotic cells. Cluster analysis revealed three metabolic profiles differentiating endosymbiotic (#1: high LPO, low lipid) and ex-symbiotic cells (#3: low LPO, high lipid), with the intermediate group (#2) containing both cell types. Heat stress caused endosymbionts of Pocillopora acuta to shift away from cluster #1, suggesting this cluster represents cells in healthy/stable symbiosis. Our study delivers a new means to assess the coral symbiosis, demonstrating that symbiont LPO ratio combined with lipid store volume is a robust metabolic marker for the state of the symbiosis at the cellular level.